Readiness for Hospital Discharge among Family Caregivers of Patients with Chronic Diseases - Fauzia, Salwa Ghaida; Kurniawan, Titis; Pratiwi, Sri Hartati; Trisyani, Mira; Pahria, Tuti (Indonesian Journal of Global Health Research, 2024)
Families often act as informal caregivers for family members who suffer from chronic diseases. Intensive family involvement improved patients’ adherence in performing post-discharge treatment program, hospital readmission, clinical outcomes, and quality of life. To effectively help the patients managing their diseases, the family caregivers required not only understand but also must be ready for helping patients manage their conditions. This study aims to identify the readiness for hospital discharge among family caregivers of patients with chronic diseases. Data were collected from 121 family caregivers recruited consecutively from adult inpatients wards using the respondents’ characteristics questionnaire and Readiness for Hospital Discharge Scale for Family with Adult Patients (RHDS Fam) questionnaire (inter-item correlation = 0.90, and Cronbach alpha 0.89). Descriptive analysis was applied. The results showed that most of family were female (77.7%%), unemployed (69.4%), graduated from senior high school (57.9%), and had no chronic diseases (86.8%). Generally, family caregivers reported high readiness for hospital discharge (7.75 Out of 10). While the coping abilities identified as the readiness domain with highest average score (9.07±1.15), the personal domain identified as the lowest domain (7.07 ±0.68). Higher readiness was showed in the age group of 20-40 years, female, graduated from senior high school, employed, and are the siblings of the patients. It can be concluded that the family caregivers of chronic disease patients are ready to return home and help patients continue their post-discharge treatment program. However, interventions are needed to improve their readiness related to patient’s personal status, particularly those who are male, lower educational background, unemployed, has a relationship as parents of the patients, and has a chronic illness.